Neuroretinal rim response to transient changes in intraocular pressure in healthy non-human primate eyes. (April 2020) - Pardon, Laura P.; Harwerth, Ronald S.; Patel, Nimesh B.
Abstract: Optic nerve head (ONH) neuroretinal rim thickness, quantified as minimum rim width (BMO-MRW), is a sensitive measure for assessing early glaucomatous disease. The BMO-MRW is sensitive to transient fluctuations in intraocular pressure (IOP), but the time course over which BMO-MRW decreases and recovers with changes in IOP remains unknown. The goal of this study was to investigate the dynamics of BMO-MRW changes over 2-h periods of mild or moderate IOP elevation, and subsequent recovery, in healthy non-human primate eyes. Eight non-human primates were included in the study. For each animal, in two different sessions separated by at least 2 weeks, the anterior chamber IOP of one eye was maintained at either 25 mmHg or 40 mmHg for 2 h and, subsequently, at 10 mmHg for 2 h. For the duration of anterior chamber cannulation, optical coherence tomography (OCT) radial scans centered on the ONH were acquired every 5 min and used to quantify BMO-MRW. An exponential decay or rise to maximum function was used to determine the extent and rate of structural change. Additionally, Bruch's membrane opening (BMO) area, BMO height/displacement, and BMO-referenced anterior lamina cribrosa surface depth (BMO-ALCSD) were computed from radial scans. A circular scan was used to quantify retinal nerve fiber layer thickness (RNFLT) and circumpapillary choroid thickness. The primary results demonstrated that the BMO-MRW changed over an extended duration, while BMO displacement was rapid and remained stable with sustained IOP. The mean maximum predicted BMO-MRW thinning following 2 h of IOP elevation was significantly related to pressure (34.2 ± 13.8 μm for an IOP of 25 mmHg vs 40.5 ± 12.6 μm for 40 mmHg, p = 0.03). The half-life for BMO-MRW thinning was 21.9 ± 9.2 min for 25 mmHg and 20.9 ± 4.2 min for 40 mmHg, not significantly different between IOP levels (p = 0.76). Subsequently, after 2 h of IOP at 10 mmHg, all animals exhibited partial recovery of BMO-MRW with similar degrees of persistent residual thinning for the two IOP levels (21.5 ± 13.7 vs 21.0 ± 12.3 μm, p = 0.88). Similar to BMO-MRW, choroid thickness exhibited gradual thinning with IOP elevation and residual thinning following IOP reduction. However, there was no significant change in BMO area or BMO-ALCSD in either experimental session. The RNFLT gradually decreased over the duration of IOP elevation, with continued decreases following IOP reduction for the 40 mmHg session, resulting in total changes from baseline of −2.24 ± 0.81 and −2.45 ± 1.21 μm for 25 and 40 mmHg, respectively (p < 0.001). The sum of the results demonstrate that the ONH neural tissue is sensitive to changes in IOP, the effects of which are gradual over an extended time course and different for increased vs. decreased pressure. Understanding the duration over which IOP influences BMO-MRW has important implications for studies investigating the effects of IOP on the ONH. Additionally, individual variability in ONH response to IOP may improve our understanding of the risk and progression of disease. Highlights: Changes in intraocular pressure result in rapid changes in the neuroretinal rim. The neuroretinal rim continues to change over a period of 2 h with sustained IOP. Residual thinning of the neuroretinal rim persists after 2 h of IOP reduction. There is individual variability in the rate and extent of rim tissue thinning.